How should minimally important change scores for the Patient‐Oriented Eczema Measure be interpreted? A validation using varied methods. (1st May 2018) - Howells, L.; Ratib, S.; Chalmers, J.R.; Bradshaw, L.; Thomas, K.S.
Summary: Eczema is common, itchy skin condition. The Patient‐Oriented Eczema Measure (POEM) is a short questionnaire that patients or parents can fill out to tell us how severe their eczema symptoms (or those of their child) are. It provides a score from 0–28. In both research and clinical practice, we are often interested to see if these scores have improved over time. This study aimed to find out what change in scores on this questionnaire mean for patients' improvements in their eczema symptoms. It looked at how 300 children in the UK answered the POEM. It calculated what level of change in scores needs to occur to show a real change in the symptoms rather than just random error in the way people have answered the questions. It also calculated the minimum change that can be seen as meaningful to patients and healthcare professionals. There are a number of different methods available for calculating this so the study included five different methods. Looking at all the results together, the researchers were able to provide some guidelines on how to interpret change in this questionnaire. If scores have changed by 2 points or fewer, this is unlikely to be a change beyond measurement error. A change of 2.1 to 2.9 points is a small change detected that is likely to be beyond measurement error but may not be clinically (medically) important. A change of 3 to 3.9 points is probably a clinically important change. A change of 4 points or over is very likely to be a clinically important change.